Importance of beta-lactam pharmacokinetics and pharmacodynamics on the recovery of microbial diversity in the airway of persons with cystic fibrosis. (October 2021) - Hahn, Andrea; Burrell, Aszia; Chaney, Hollis; Sami, Iman; Koumbourlis, Anastassios C; Freishtat, Robert J; Zemanick, Edith T; Louie, Stan; Crandall, Keith A
Cystic fibrosis (CF) is a chronic lung disease characterized by acute pulmonary exacerbations (PExs) that are frequently treated with antibiotics. The impact of antibiotics on airway microbial diversity remains a critical knowledge gap. We sought to define the association between beta-lactam pharmacokinetic (PK) and pharmacodynamic target attainment on richness and alpha diversity. Twenty-seven children <18 years of age with CF participated in the prospective study. Airway samples were collected at hospital admission for PEx, end of antibiotic treatment (Tr), and >1 month in follow-up (FU). Metagenomic sequencing was performed to determine richness, alpha diversity, and the presence of antibiotic resistance genes. Free plasma beta-lactam levels were measured, and PK modeling was performed to determine time above the minimum inhibitory concentration ( f T>MIC). 52% of study subjects had sufficient f T>MIC for optimal bacterial killing. There were no significant differences in demographics or PEx characteristics, except for F508del homozygosity. No significant differences were noted in richness or alpha diversity at individual time points, and both groups experienced a decrease in richness and alpha diversity at Tr compared with PEx. However, alpha diversity remained decreased at FU compared with PEx in those with sufficient f T>MIC but increased in those with insufficient f T>MIC (Shannon −0.222 vs +0.452, p=0.031, and inverse Simpson −1.376 vs +1.388, p=0.032). Fluoroquinolone resistance was also more frequently detected in those with insufficient f T>MIC (log2 fold change (log2FC) 2.29, p=0.025). These findings suggest sufficient beta-lactam f T>MIC is associated with suppressed recovery of alpha diversity following the antibiotic exposure period.